Successful Implementation of Thai Family Matters: Strategies and Implications - Michael J. Rosati (2018)
This article discusses the successful process used to assess the feasibility of implementing the Family Matters program in Bangkok, Thailand. This is important work since adopting and adapting evidence-based programs is a strategy currently endorsed by leading prevention funding sources, particularly in the United States. The original Family Matters consists of four booklets designed to increase parental communication with their adolescent children in order to delay onset of or decrease alcohol, tobacco, and other drug use. As part of the program, health educators contact parents by telephone to support them in the adoption of the program. Each booklet addresses a key aspect of strengthening families and protecting young people from unhealthy behaviors related to alcohol and other drug use. Adaptation of the program for Bangkok focused on cultural relevance and the addition of a unit targeting adolescent dating and sexual behavior. A total of 170 families entered the program, with the majority (85.3%) completing all five booklets. On average, the program took 16 weeks to complete, with families reporting high satisfaction with the program. This article provides greater detail about the implementation process and what was learned from this feasibility trial. © 2012 Society for Public Health Education.